A Simplified Mortality Score Using Delta Neutrophil Index and the Thrombotic Microangiopathy Score for Prognostication in Critically Ill Patients. Issue 1 (January 2018) - Goag, Eun K.; Lee, Jong W.; Roh, Yun H.; Leem, Ah Y.; Kim, Song Y.; Song, Joo H.; Kim, Eun Y.; Jung, Ji Y.; Park, Moo S.; Kim, Young S.; Kim, Se K.; Chang, Joon; et al.
ABSTRACT: Background: This study was conducted to assess the prognostic value of a simplified mortality score (SMS) using the delta neutrophil index (DNI) and thrombotic microangiopathy (TMA) score, both easily obtained from the complete blood count, to identify critically ill patients at high risk of death. Methods: This was a retrospective study performed in the medical ICU at Yonsei University College of Medicine from June 2015 to February 2016. The primary end point was 28-day all-cause mortality. Participants were divided into two groups: a training (n = 232) and a test (n = 57) set. We used Cox proportional-hazards analysis, Harrell's C index, and Kaplan–Meier survival analysis to derive the SMS and test its internal validity. Results: We enrolled 289 patients. The 28-day mortality rate was 31.1% (n = 90). Nonsurvivors had higher APACHE II, SOFA, and TMA scores, and DNI. The SMS, derived by Cox proportional-hazards analysis, consisted of age, sex, DNI, and TMA score. We assigned a weighted point to each variable in the SMS, as follows: age + 11 if male + (2 × DNI) + (61 [TMA = 1], 76 [TMA = 2], 74 [TMA = 3], 26 [TMA = 4], 99 [TMA = 5]). Nonsurvivors had a higher median SMS than survivors, and the Harrell's C index was 0.660. Analysis of survival by risk group according to SMS (low, intermediate, high risk) showed a significant difference among these three groups ( P < 0.001). We then investigated this SMS in the test set to determine internal validity; the results were similar to those of the training set. Conclusions: The SMS is a more rapid, simple prognostic score for predicting 28-day mortality and stratifying risk than the APACHE II or SOFA scores. However, external validation using a larger sample is needed.